Factors affecting the intention to adopt BYOD among healthcare professionals in Pakistan - Nisar, Saima; Sheik Osman, Wan Rozaini (2016)
Portable devices have emerged as a vital technological device in healthcare.These mobile devices have mobile telecommunication also internet accessibility and word processing. These devices have additional features relevant to healthcare needs and practice.Studies associated with mobile technology adoption among healthcare professionals (HCP) in Pakistan are comparatively very little.The purpose of this study is to investigate the factors that affect HCP intention to adopt BYOD.In this paper, the researchers provide a direction for future research to understand and study the relationship of factors affecting BYOD adoption.Finally, this study also presents the variables that affect HCP attitude towards adopting BYOD.